Złożoność zjawiska mowy nienawiści w pozaprawnym aspekcie definicyjnym - Rogalska, Ewelina; Urbańczyk, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The starting point is thinking that the modern political debate manifests in the degradation of the culture of discussion. One of the issues that can be observed next to this phenomenon is the brutalization of the language of public debate — hate speech is becoming more and more common.The aim of the paper is the description and the characteristic of vital aspects which appear in accordance to the designation of hate speech and its manifestations in public sphere.
Keywords: mowa nienawiści; podżeganie do nienawiści; wolność słowa; granice wolności słowa; faszyzm; rasizm; antysemityzm; teoria istotności; ksenofobia; prawo dyskryminacyjne; Allport, Gordon